Web-Based Paskibra Member Recruitment and Selection Management Information System in Islamic Universities - Sabri, Muhammad; Suendri, Suendri; Putri, Raissa Amanda (Jurnal Penelitian Medan Agama, 2025)
This study aims to overcome problems in the process of accepting and selecting new members of Paskibra UIN North Sumatra by building a management information system. Paskibra UIN North Sumatra is one of the intra-campus organizations under the auspices of UIN North Sumatra. This organization has a system for accepting and selecting new members. However, in its implementation, this process often experiences obstacles, such as loss of prospective member data and delays in selection and announcement of results. A web-based Paskibra member acceptance and selection management information system at UIN North Sumatra was built to facilitate management in the process of acceptance, selection, and announcement of results. This information system allows registration to be done online, so prospective members do not need to come in person. In addition, the Board of Trustees can more easily monitor the selection process and provide more systematic assessments. Data collection techniques used include observation, interviews, and literature studies. The system development method applied is the Waterfall model. The system design is carried out using UML (Unified Modeling Language) to define the system workflow. The results of this study are a management information system that can increase efficiency in the process of accepting and selecting prospective Paskibra members. This information system can help reduce the risk of data loss, speed up the selection process, and improve accuracy in the assessment and announcement of results. With the information system in this study, the Paskibra UIN Sumatera Utara management can carry out its duties more optimally and provide convenience for prospective members in participating in the selection process. This research is important in encouraging the digital transformation of student organizations because it can increase work efficiency and effectiveness, as well as strengthen transparency and accountability in the selection process for new members.